Attention to Linguistic Diversity in the Spanish Context: Policies, Plans and Actions - Barranco Izquierdo, Natalia (2019)
The authors approach the notion of attention to linguistic diversity from a socio-institutional perspective, as one of the priority axes in the Education and Training systems in the member states of the European Union for the achievement of quality education. A selection of national official documents is offered that are linked to this notion. The authors identify those institutional plans and actions conceived by the different Autonomous Communities –monolingual and bilingual– that address the linguistic needs of foreign students.